Verantwoordbaarheid in maatskaplike sorg: 'n Konseptuele analise - Van Niekerk, AA (Social Work/Maatskaplike Werk, 2002)
In this article, the concept of "accountability" is submitted to a philosophical conceptual analysis, pertaining, in particular, to its relevance for social work. The author argues that the concept gains a ctuality in our current situation because of the increase in violent and white-collar crime, but also because accountability is an inevitable desideratum of a process of democratization. He analyzes the concept with reference to its meaning in the close interaction between individual an community, the tension between autonomy and limitless freedom, the moral demand that acts be universalizable, and the need for a self-critical attitude. He goes on to analyze the similarities and differences between accountability and responsibility, drawing on work done by Hans Jonas on responsibility. He concludes with remarks on the instances/parties to whom social workers are accountable, and, in this connection, distinguishes between five kinds of accountability, viz. administrative, political, collegial, professional and moral.